Continuing professional development requirements for UK health professionals: a scoping review. Issue 3 (10th March 2020) - Karas, Marek; Sheen, Nik J L; North, Rachel V; Ryan, Barbara; Bullock, Alison
Abstract : Objectives: This paper sets out to establish the numbers and titles of regulated healthcare professionals in the UK and uses a review of how continuing professional development (CPD) for health professionals is described internationally to characterise the postqualification training required of UK professions by their regulators. It compares these standards across the professions and considers them against the best practice evidence and current definitions of CPD. Design: A scoping review. Search strategy: We conducted a search of UK health and social care regulators' websites to establish a list of regulated professional titles, obtain numbers of registrants and identify documents detailing CPD policy. We searched Applied Social Sciences Index and Abstracs (ASSIA), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Medline, EMCare and Scopus Life Sciences, Health Sciences, Physical Sciences and Social Sciences & Humanities databases to identify a list of common features used to describe CPD systems internationally and these were used to organise the review of CPD requirements for each profession. Results: CPD is now mandatory for the approximately 1.5 million individuals registered to work under 32 regulated titles in the UK. Eight of the nine regulators do not mandate modes of CPD and there is little requirement to conduct interprofessional CPD. Overall 81% of those registered are required to engage in some form of reflection on their learning but only 35% are required to use a personal development plan while 26% have no requirement to engage in peer-to-peer learning. Conclusions: Our review highlights the wide variation in the required characteristics of CPD being undertaken by UK health professionals and raises the possibility that CPD schemes are not fully incorporating the best practice.